A Synopsis of some Recent Name Changes in Plants of the Indian Subcontinent - Rao, R. R.; Jain, S. K. (Indian Forester, 1979)
The changes in names of about 50 plants, pablished in recent taxonomic literature are enumerated Some selected synonyms including basionyms are given.